Simulation study of reactive distillation using Aspen plus for the production of MTBE - Nik Rozaimah, Salim (2010)
Methyl tertiary butyl ether (MTBE) is a chemical compound that widely used as an octane enhancer in gasoline blending in order to improve hydrocarbon efficiency. It has a low vapor pressure and can be blended with other fuels without phase separation. It has the desirable octane characteristics. In the oxygenate group, MTBE is attractive for a variety of technical reasons. MTBE is produced via direct addition of methanol to isobutylene using sulfonated ion exchange resin as catalysts. There are several of ways that can be used to produce MTBE such as conventional method. This process involves reactor and separate distillation column units. Another method for the production of MTBE is introduced by Smith in the 1980. It is a combination of reactor and distillation column in the one system and improvement of conventional method. Main objective of this research are to develop a simulation model of reactive distillation for production of MTBE using Aspen Plus as a modeling platform. This research also study on the effect that affected the design and operating condition of the column. It started with finding the mathematical models that suitable for the simulation and substitute in the simulation software which is ASPEN Plus. Analysis and observation has been performed after the simulation converges and complete. Based on the result that obtained from simulation, main factors that can affect the conversion in MTBE production was majorly from Isobutylene condition. Manipulation of the inlet temperature in the both stream does not affect the condition of the column. Changes of Isobutylene feed composition contribute a lot in the increment of the conversion of methanol. Conversion of the process increase from 75.8% until 94% when feed composition of Isobutylene changing from 0.25 until 0.57.